Quality improvement of food products using taguchi method: a study in a bread product SME - Alifin, Fakhri Ikhwanul; Rahma, Rana Ardila; Sadidan, Ikhwanussafa; Fitriani, Risma (Universitas Mercu Buana, 2023)
Quality is one of the most crucial factors for manufactured products. Good product quality will increase customer loyalty and hence, higher profit for the company. SR company is a local Small Medium Enterprise (SME) in Bandung that produces bread products. Among various kinds of bread, Kadet is the main product with an average production of approximately 1000 pcs per day. In addition, Kadet bread has numerous defective products with an average of 3%-5% per 1000 pcs. Moreover, Kadet is a product baked at high temperatures, and hence, the timing of the production staff is crucial to prevent defectiveness. In this work, we use the Taguchi method to obtain factors that produce defectiveness and the combination of the optimal production factors. Furthermore, using the Analysis of Variance, the results show the optimal process design for minimum defective Kadet bread products as the process evaluation for better product quality.